2019
DOI: 10.1002/marc.201800874
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Coatings Based on Renewable White Dextrins and Isocyanate Trimers

Abstract: The polyurethane industry is strongly dependent on fossil‐based polyols and polyisocyanates. Developing novel sustainable polyols from valuable biobased building blocks is a first step toward strong and durable development. The synthesis and properties of PU films based on pristine and acylated white dextrins (AVEDEX W80) as polyol and an aliphatic, low‐viscosity, solvent‐free triisocyanate based on hexamethylene diisocyanate (trimer—Desmodur N3300) as crosslinker is reported. After optimizing several conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In our previous work, we found that pristine AVEDEX W80 resulted in the best PU films [ 29 , 48 ] (i.e., with no cracks, inhomogeneity, or swelling) and we, therefore, continue with this system and two bio-based isocyanates—ethyl ester l -lysine diisocyanate (LLDI) and ethyl ester l -lysine triisocyanate (LLTI)—and one commercial isocyanate—isophorone diisocyanate (IPDI). The optimal reaction conditions in terms of casting time and temperature, isocyanate used, amount of solvent, and excess of isocyanate were also determined.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that pristine AVEDEX W80 resulted in the best PU films [ 29 , 48 ] (i.e., with no cracks, inhomogeneity, or swelling) and we, therefore, continue with this system and two bio-based isocyanates—ethyl ester l -lysine diisocyanate (LLDI) and ethyl ester l -lysine triisocyanate (LLTI)—and one commercial isocyanate—isophorone diisocyanate (IPDI). The optimal reaction conditions in terms of casting time and temperature, isocyanate used, amount of solvent, and excess of isocyanate were also determined.…”
Section: Introductionmentioning
confidence: 99%
“…When no standards of known purity are commercially available, the two most commonly used approaches are either to synthetize or isolate them from a known matrix. Some examples exist already in the literature related with FCM oligomers [6,7,8]. However, to the best of the author’s knowledge, no analytical standards for the individual PBT cyclic oligomers are yet commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Diol derivatives (α,ω-telechelic diols) are especially targeted due to the feasibility of the hydroxyl end groups to react with different functional groups. At this point oligomer diols are industrially mainly synthesized via depolymerization routes. Polyethylene terephthalate (PET) oligomeric diols are frequently produced by depolymerization via glycolysis. This process is used to upgrade recycled PET via postcondensation of PET diols.…”
Section: Introductionmentioning
confidence: 99%